SOSIALISASI DIVERSIFIKASI PRODUK PENGOLAHAN HASIL PERIKANAN DI DESA BIDO, KECAMATAN MOROTAI JAYA - Olivia Akerina, Febrina; Saubati, Deriksen (HIRONO : Jurnal Pengabdian Masyarakat, 2025)
High Perishable Food is a type of food that has fast-rotting properties, and fish is one type of that food. This is influenced by the activity of enzymes and bacteria that are naturally present in the fish’s body. Bido Village is one of the villages located in the North Morotai District, which is located on the beach. The village fisheries potential is dominated by skipjack, julung-julung, and tuna. The main problem faced in Bido Village is the abundance of fishery products, but it is not balanced with community knowledge related to good handling and processing. This activity aims to inform the public about the diversification of fishery product processing, which has an impact on increasing the knowledge of the people of Bido Village. Counseling activities are carried out by delivering material in the form of potential fishery products and the processing of fishery products. Evaluation activities are carried out in the form of questions and answers on the material presented. The participants who attended were enthusiastic about hearing the material presented, as shown by several questions related to the type of processing that could be made from tuna and julung-julung fish. In general, participants of the service activity have increased knowledge about what processed products can be made from fish caught by fishermen.